Mental Health and Eudaimonic Well-Being in Digital Age - Nishtha Pandey; Victoria Susan Ijjina (The Bioscan, 2024)
The digital age has both positive and negative effects on mental health and eudaimonic well-being. On the one hand, technology provides access to information and support, enhancing relationships. On the other hand, excessive screen time, social media and digital stress can contribute to mental health issues. Nowadays, adolescents are spending more and more of their time online and are connected via digital technologies Mobile device ownership and social media use have reached unprecedented levels and concerns have been raised that this constant connectivity is affecting people's mental health and wellbeing. A balance and conscious use of technology is crucial to promoting overall well-being in the digital age but the use of social media and internet is increasing and along with it many negative effects are also being seen. Also, spending a lot of time on social media and mobile devices can divide students' attention and prove to be a distraction. Being engaged on social media for a long time may affect their ability to concentrate and they may struggle in studies. Compared to meeting the norms of visual, life and physical consistency on social media, they may be weaker in terms of self-assessment and conceptualization. Excessive scrolling, wasteful apps, and online entertainment can distract students and affect their studies. Social media can create a sense of selfishness, unpredictability, and dissatisfaction among the younger generation. Due to the display of high lifestyle and attractive appearance on Instagram, Facebook and other social media platforms, adolescents may remain dissatisfied with their self-esteem. This paper reviews mental health and eudaimonic well-being in digital age.